Maskulinitas dan Perjuangan Hidup Laki-laki: Analisis Kritis van Dijk pada Lagu “Anak Lanang” Ndarboy Genk - Anggra Dini; Mulyana Mulyana; Endang Nurhayati (Javanese Language, Literature, and Culture Study Program, Universitas Gadjah Mada, 2025)
A song, as a form of art, offers learning opportunities for its listeners through the messages conveyed by the songwriter. The song